Evaluating task-based syllabus for EFL learners - Luu, Hoang Mai; Luu, Thi Bich Ngoc (Brazilian English Language Teaching Journal)
This research is an evaluation of the effectiveness of task-based syllabus on EFL learners’ language competence at a private university in Vietnam educational context. This research resorts to questionnaire survey, semi-structured interview, and pretest and posttest as instruments for data collection. The research findings revealed that a strength of the current task-based syllabus is the match between lesson topics and students’ expectations. However, the syllabus still created difficulties for students including insufficient vocabulary, unfamiliar structures, and lack of life knowledge. The effect of teaching with task-based syllabus on students’ language performance is also reflected through a significant difference in mean scores between the pretest and the posttest. This research provides an insight into the effectiveness of English teaching through task-based syllabus at a private university in Vietnam setting. It implies to teachers that they need to be sustainable change catalysts for more interesting syllabus for learners